Estimation of kinetic parameters for enzyme-Inhibition reaction models using direct time-dependent equations for reactant concentrations - Goličnik, Marko (Acta chimica slovenica, 2012)
To facilitate the determination of a reaction type and its kinetics constants for reversible inhibitors of Michaelis-Mententype enzymes using progress-curveanalysis, I present here an explicit equation for direct curve fitting to full time-course data of inhibited enzyme-catalyzed reactions. Thisalgebraic expression involves certain elementary functions where their values are readily available using any standard nonlinear regression program. Hence this allows easy analysis of experimentally observed kinetics without any data conversion prior to fitting. Its implementation gives correct parameter estimates that are in very good agreement with results obtained using both the numerically integrated Michaelis-Menten rate equation or its exact closed-form solution which is expressed in terms of the Lambert W function.
Keywords: Catalysis; Časovni faktorji; encimske reakcije; Encimski inhibitorji; Enzyme Inhibitors; inhibicije; Kataliza; kemijska kinetika; Kinetics; Kinetika; Michaelis-Menenova kinetika; Modeli teoretski; Models, Theoretical; Nelinearna dinamika; Nonlinear Dynamics; Time Factors